Effect of plyometric training by using the interval circular training method on the development of explosive power of the lower limbs of handball players under 19 years. - شادي عبد الرزاق; بشير حسام (Journal of Sport Science Technology and Physical Activities, 2025)
This study aimed to prove the influence of plyometric training and his role in the development of the explosive power of the lower limbs to handball players. The study sample consisted of handball players. The researchers used the experimental method. These data were processed using Stat Plus v 2007. The study found the following results: - Plyometric training and regular training has an effective impact on developing the explosive power of the lower limbs to handball players. However, Plyometric training have more effectiveness